Digitalisation of Micro, Small, and Medium Enterprises (MSMEs) in Tourism Villages - Muhamad Dani Somantri; Moh. Yusup Saepuloh Jamal; Ridwan Saepul Aripin (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The digitalization of tourism village MSMEs in Guranteng, Tasikmalaya Regency, was done using online platforms for the assisted community in the processed food category. The objectives of this assistance are to (1) explore various aspects of excellence (potential assets) owned by the tourism village MSME community in Guranteng Village, Pagerageung District, Tasikmalaya Regency, (2) provide comprehensive business management development assistance to 20 tourism village MSME groups in Guranteng Village through the application of digital technology, and (3) realize effective, efficient, and adaptive management of tourism village MSMEs to the digital world to boost family economic improvement. The assistance was provided using the ABCD method, prioritizing utilizing local superior assets through discovering, dreaming, designing, and determining. The results of the service included providing assistance and training on obtaining business registration numbers (NIB), food production licenses (PIRT), halal certification, labelling, packaging, promotion, and digital marketing through social media and the Shopee Application.